Codified Ordinances of the City of Cleveland, at 37, Ch. 10, §12, pt. 6 (1877) - (:unkn) unknown (General Publisher, 1877)
No person shall discharge any fire arms within the cemeteries, except at military funerals."
--
Keywords: DISCHARGE